An analysis of public school teachers' salary schedule under the Wage and Position Classification Office (WAPCO) and of its implementation - Valino, Rosalinda S. 1918- (s.n.], 1965)
This is an analysis of salary schedules and the principles and criteria that served as the bases for its creation. The operation of the schedule has been scrutinized and it yields attendant problems to its implementation.